Drinking water requirements for lactating dairy cows - John F. Smith; Joseph P. Harner; S.R. DeFrain; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2001)
A study to determine the amount and location of water consumption in dairy freestall barns located in northeastern Kansas was conducted during the summer of 2000. Three farms, two Holstein farms with either 2-row or 4-row freestall barns and one Jersey farm with 4-row freestall buildings, were used. Summer water usage averaged 30 to 40 gallons per Holstein cow/day and 20 to 40 gallons/cow/day for Jersey cows depending on age and stage of lactation. The farms with Holstein cows had a water usage ratio of 4 to 4.5 lb of water per lb of milk produced and Jersey cows required 3.1 lb of water per lb of milk production. However, at the Holstein dairies, only about 85% of this water was consumed and the other 15% was utilized to refill the tanks after tipping twice daily to clean cross-overs and water troughs. In addition, 35 to 45% of the water consumed is from a water station in the center crossover of each pen. Cattle also drank the least amount of water from the trough located in the crossover furthest from the pen entrance. When given access to a water trough on the milking parlor exit, cattle consumed 10% (3.5 gallons/cow/day) of the daily water intake at this location. Water usage for drinking increased as milk production increased. Adequate water system capacity and water rights are needed to make allowances for future increases in milk production. Water consumption was greater at the center alleys. Therefore, engineers should consider additional space and/or water troughs at these watering stations.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Water consumption; Heat stress; Cow comfort